2004
DOI: 10.1159/000082355
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Estrogen on Melanocortin-3 Receptor mRNA Expression in Mouse Pituitary Glands in vivo and in vitro

Abstract: Alpha-melanocyte-stimulating hormone (α-MSH) stimulates prolactin (PRL) release and mammotrope proliferation in mouse anterior pituitary glands. The present study investigated the regulation of melanocortin-3 receptor (MC3-R) mRNA levels in mice using semi-quantitative reverse transcriptase-polymerase chain reaction (RT-PCR) analysis. Relative MC3-R mRNA levels in the anterior lobes of female mice increased between 20 and 45 days of age, and a significant difference in MC3-R mRNA expression between sexes was s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 60 publications
1
5
0
1
Order By: Relevance
“…Dmrt1a, Dmrt1b, Foxl2, Cyp19a, and Cyp19b mRNA levels were expressed relative to that of b-actin in each sample. In our study, b-actin expression was found to be unaffected by the drug treatment, as reported previously for E 2 (Matsumura et al 2004) and TAM (Parte et al 2002).…”
Section: Drug Treatmentsupporting
confidence: 91%
“…Dmrt1a, Dmrt1b, Foxl2, Cyp19a, and Cyp19b mRNA levels were expressed relative to that of b-actin in each sample. In our study, b-actin expression was found to be unaffected by the drug treatment, as reported previously for E 2 (Matsumura et al 2004) and TAM (Parte et al 2002).…”
Section: Drug Treatmentsupporting
confidence: 91%
“…65,83 Investigação dos receptores de estrogênio, na epiderme e nos melanócitos das peles sã e lesada, seria esclarecedora quanto ao papel de hormônios esteróides sexuais, no processo da hiperpigmentação localizada da doença. [84][85][86][87][88] Pesquisa de variantes alélicas do MC1-R, que se expressem diferentemente na pele sã e lesada, poderiam justificar a pigmentação mais efetiva, em certas áreas fotoexpostas, do que em outras. 30,46,89 Cultura de ceratinócitos e melanócitos, de pele sã e com melasma e de populações não acometidas pela doença, sob diferentes regimes de exposição, permitiria um estudo comparativo da expressão de diversos genes para demonstrar as bases do comportamento fenotípico diferente desses grupos de células adjacentes, no mesmo tecido.…”
Section: Considerações Finaisunclassified
“…A previous study indicated that E2 stimulated MC3R gene expression in vivo (Matsumura et al, 2004). Therefore, we investigated the effects of E2 on the Mc3r promoter activity.…”
Section: Effect Of E2 On Mouse Mc3r Gene Expression and Its Promoter mentioning
confidence: 96%
“…The Mc3r mRNA levels in female pituitaries are higher than in male pituitaries. In mouse pituitaries, in the female mouse anterior pituitary Mc3r mRNA expression is regulated by estrogen (Matsumura et al, 2004). However, it is not clear whether estrogen directly or indirectly regulates Mc3r transcription.…”
Section: Introductionmentioning
confidence: 99%